Anxiety disorder: A bibliographical review of 21st century evil - Fonseca, Pedro Augusto Resende da (Seven Editora, 2023)
Given the great harm that anxiety disorder can cause in society, such as family members, love and interpersonal relationships of friendship and work, and especially in individuals who have it. This work aimed to collect data from scientific journals and scientific books to address the topic in a clear and objective way, about one of the great evils of the 21st century. The work also seeks to increase the bibliographic collection on the subject, thus reinforcing the need to study anxiety disorder. DOI:https://doi.org/10.56238/sevened2023.006-012